Exploring the design and contributions of urban agroecosystem living labs for sustainable city development - Diego Alejandro Riaño-Herrera; Felipe Romero-Perdomo; Juanita Quintero-Castro; Alejandra García-Sánchez; Leonardo Rodríguez-Urrego (Sustainable Futures)
Living Labs are open innovation ecosystems within real-life settings, designed to address societal challenges through iterative feedback processes. In the context of promoting sustainable cities, the Urban Agroecosystem Living Labs (UALLs) has garnered increasing attention. This study investigates how UALLs are designed and what their contributions are to promoting the sustainable transition of cities. This was achieved by mapping UALLs identified in both academic and gray literature. Subsequently, a qualitative assessment of their design was conducted, focusing on their aims, processes, activities, and participants. Their alignment with the Sustainable Development Goals (SDGs) and their contribution to urban sustainability were also explored. The study identified 34 UALLs, which exhibit a remarkable diversity in their design. Besides boosting agricultural productivity and food security, UALLs help shape sustainable cities by promoting responsible food consumption, enhancing community cohesion and resilience, improving greening and biodiversity, supporting climate mitigation, and reducing waste. The most notable UALLs were the AU/LAB Centre for Co-creation and Innovation Opened for Urban Agriculture in Canada, ILVO Living Lab Agrifood Technology in Belgium, and the RUBA Living Lab in Colombia, with holistic approaches that address ecological, economic, and social aspects of urban environments. However, UALLs must align their strategies with the SDGs and strengthen the measurement of their contributions. This paper encourages broader adoption of UALLs, improving its design while expanding its influence in the pursuit of sustainable cities.